Women in Prostitution and Social Responsibility - Margrit Brückner (Social Work & Society, 2008)
The aim of the paper is to show how prostitution is embedded in historically changing gender relationships regulated by the state and part of each societies understanding of sexuality. An important role to improve the situation of women in prostitution is played by engaged social work, often linked to the womens movement on a local, national and an international level in spite of differing positions on the institution of prostitution. The authors argumentation is based on qualitative and quantitative empirical findings concerning shared experiences as well as differences between women in prostitution and findings on professional possibilities and limits of supporting the women. Important dimensions of heterogeneity amongst the women are legality versus illegality, decision making possibilities respectively dependencies und choice versus force, which also are the base of different political and professional positions taken by experts.